The Effect of Celebrity Endorsers and Brand Image on Purchase Decision - Nizar Alam Hamdani; Aura Rahayu; Dewi Anggraen; Intan Permana (Cita Konsultindo Research Center, 2024)
Making purchasing decisions is crucial for businesses as it can increase profits through effective product marketing. On the other hand, poor purchasing decisions can hinder achieving a high market share percentage. This study examines the impact of celebrity endorsers and brand image on purchasing decisions related to marketing. The target population of this particular study was Indonesian society, specifically users of Emina moisturizer products between the ages of 15 and 25. The survey was conducted online and face-to-face, with a total of 747 individuals being randomly selected from the population to represent the sample. This quantitative study used a statistical approach to analyze the collected data. The statistical product and service solution (SPSS) program was used to perform regression analysis, as it met the criteria required for this type of data analysis. An interval scale was utilized to ensure accuracy in the regression analysis. The data obtained in this study was accurate and reliable, with a significance level of 95%. The research findings indicate that celebrity endorsers are significantly influenced by brand image, which is crucial in purchase decisions. Celebrity endorsers and brand image are essential for boosting sales, promoting loyalty, and attracting new consumers.